Fabrication and Characterization of Calcium-Phosphate Lipid System for Potential Dental Application - Zhu, Ningxin; Wang, Dan; Xie, Fei; Qin, Man; Lin, Zhiqiang; Wang, Yuanyuan (Frontiers in Chemistry, 2020)
Lipid has been widely studied as vehicle and loading vector, but there was no reports of related application in dental field. The purpose of this research was to fabricate and characterize a nano-size calcium-phosphate lipid (CL) system as a potential vehicle in dental regeneration study, the biocompatibility with dental pulp stem cells (DPSCs) was evaluated. The effect of CL on DPSCs proliferation was analyzed by CCK-8 assay, and the anti-inflammatory effect was investigated by quantitative polymerase chain reaction (qPCR). Moreover, the effect of CL on odontogenic differentiation of inflamed DPSCs (iDPSCs) was studied by Alizarin red staining, tissue-nonspecific alkaline phosphatase (TNAP) staining, qPCR, and western blot analyses. The results of this study showed that CL did not affect the proliferation of DPSCs, it down-regulated the inflammatory-associated markers (IL-1β, IL-6, TNF-α, COX-2) of DPSCs treated with Escherichia coli lipopolysaccharide (LPS), and enhanced the in-vitro odontogenic differentiation potential of iDPSCs. This novel biomaterial has a broad application prospect for its bioactivity and flexible physical property, thus represents a promising pulpal regeneration material.